Toxic relationship: Rational emotive behavior therapy - Sejati, Sugeng; Isnaini, Desi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
There are many problems that occur in unhealthy relationships and the research aims to see how far rational emotive behavior therapy (REBT) can prevent toxic relationships, the research approach used is the field research method (qualitative) data sources are obtained from interviews and observation to respondents. The results of the study show that rational emotive behavior therapy has a significant impact on the handling of unhealthy relationships experienced by respondents. Providing rational emotive behavior therapy services can change the attitudes, perceptions and ways of thinking of irrational counselees to become rational and eliminate self-destructive emotional disturbances.